Method for judging pegmatite lithium mineralization potential by using tourmaline

CN122901294APending Publication Date: 2026-10-13CHINA UNIV OF GEOSCIENCES (WUHAN) +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611075851.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-20
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0003]在造山带伟晶岩密集区,系统采样结合化学分析虽可识别Li成矿潜力,但面临三重技术瓶颈:(1)效率与成本制约:造山带伟晶岩分布广泛,全量化验分析耗时耗力,难以满足大规模靶区筛查需求;(2)样品代表性质疑:伟晶岩矿物颗粒粗大(厘米级至米级),导致单一样品易出现成分不均一现象(如锂辉石局部富集),常规碎样分析可能遗漏矿化信息;(3)预判能力不足:未发育锂辉石标志性矿物的低演化岩体,其全岩分析结果仅能确认"有无矿化",无法量化成矿潜力

Benefits of technology

本发明提供了一种利用电气石判断伟晶岩锂成矿潜力的方法,通过对伟晶岩中的电气石进行微量元素以及Li和B同位素分析,判别结晶分异程度和流体出溶作用,进而判断伟晶岩成矿潜力;该方法可有效降低矿产勘探周期,最大限度压缩勘探成本,对环境没有破坏,预测的准确性有保障,克服了传统方法具有一定间接性和猜测性的难点,为矿床尺度的找矿勘探提供了理论依据,有效降低勘探风险,具有广泛的应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application discloses a method for judging pegmatite lithium mineralization potential by using tourmaline, and belongs to the field of mineral exploration and evaluation. The Li-B isotopes and trace elements are combined and analyzed to respectively perform crystallization differentiation degree and fluid exsolution discrimination: if, in the crystallization differentiation stage, δ 7 Li and δ 11 B remain stable, that is, the change amplitude of Li and δ 11 B in the stage is respectively ≤5.0‰ and ≤2.0‰, and only Li gradually enriches, it is reflected that strong crystallization differentiation is experienced; if, in the fluid exsolution stage, the stage average value of δ B is significantly reduced by ≥1.5‰ compared with the crystallization differentiation stage, and the Li content rapidly rises to ≥9000 ppm, it is indicated that the fluid exsolution process occurs in the late crystallization differentiation stage; and if the above conditions are simultaneously satisfied, it can be judged that the pegmatite system has the mineralization potential. The application has the advantages of short test period, low overall cost, accurate judgment, green environmental protection, provides a theoretical basis for deposit scale prospecting and exploration, and effectively reduces exploration risks.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of mineral exploration and evaluation, and specifically relates to a method for judging the lithium mineralization potential of pegmatites using tourmaline. Background Technology

[0002] Pegmatite-type lithium deposits, as strategically important metallic mineral resources, are not only one of the main sources of global lithium supply, but also an indispensable raw material guarantee for promoting new energy vehicles, energy storage technologies, and the low-carbon energy transition. While pegmatites are widely distributed globally, identifying which ones have the potential to form lithium deposits is exceptionally difficult. Generally speaking, the formation of pegmatite-type lithium deposits requires two key conditions: crystallization differentiation and fluid exsolution. Crystallization differentiation is the basis for initial lithium enrichment. During the evolution of granitic magma, as major rock-forming minerals such as feldspar and mica crystallize and separate, the residual magma gradually evolves towards being rich in silica, alkali, and volatiles (such as H₂O, F, P, and B), and incompatible elements such as lithium are also progressively enriched in the residual melt. This extreme differentiation not only significantly lowers the solidus temperature of the magma and prolongs the crystallization time, but also greatly enhances the migration capacity and elemental activity of the melt, prompting large-scale accumulation of lithium in the latest stage of magma evolution. Fluid exsolution is a crucial step in the large-scale enrichment and precipitation of lithium in the late mineralization stage. When a magmatic system rich in volatiles (such as H2O, CO2, F, Cl, B, and P) reaches volatile saturation due to crystallization differentiation, an independent hydrothermal fluid phase separates from the magma. This process plays multiple important roles in the final mineralization of lithium: First, lithium, as a strongly incompatible element, has high solubility in fluids and can be efficiently extracted from the magmatic phase into the exsolution-bearing fluid; second, the exsolution fluid has high mobility and low viscosity, enabling it to migrate long distances along tectonic fractures, transporting lithium to favorable tectonic spaces far from the parent rock; third, the sudden drop in pressure and temperature during fluid exsolution disrupts the original chemical equilibrium, triggering rapid crystallization and precipitation of lithium minerals (such as spodumene and petalite); simultaneously, the mineralizing agents such as F and P abundant in the exsolution fluid can further stabilize the existence of lithium in the fluid phase, improving lithium transport efficiency. Therefore, exsolution is not only a crucial bridge for transferring lithium from magmatic reservoirs to the mineralization system, but also a core mineralization process controlling the emplacement space, ore grade, and mineral assemblage of pegmatite-type lithium deposits. Thus, determining whether a pegmatite has the potential to form a high-grade lithium deposit hinges on ascertaining whether it has undergone intense crystallization differentiation to reach lithium saturation, and whether effective exsolution has occurred. These two processes jointly constrain the formation and enrichment level of pegmatite-type lithium deposits.

[0003] In areas with dense pegmatites in orogenic belts, although systematic sampling combined with chemical analysis can identify Li mineralization potential, it faces three technical bottlenecks: (1) Efficiency and cost constraints: pegmatites are widely distributed in orogenic belts, and full-scale analysis is time-consuming and labor-intensive, making it difficult to meet the needs of large-scale target area screening; (2) Questioning of sample representativeness: pegmatite mineral particles are coarse (centimeter to meter), which makes it easy for single samples to have uneven composition (such as local enrichment of spodumene), and conventional fragment analysis may miss mineralization information; (3) Insufficient predictive ability: for low-evolution rock bodies that have not developed spodumene marker minerals, the whole-rock analysis results can only confirm "whether or not mineralization exists", and cannot quantify mineralization potential.

[0004] In addition, the lithium mineralization potential of pegmatite is essentially controlled by two processes: the degree of differentiation and evolution of pegmatite and fluid exsolution. Traditional geochemical indicators have the following significant limitations: (1) Differentiation indicators fail: Although key ratios such as Mg / Li, K / Rb, and Nb / Ta can characterize the intensity of melt differentiation, they are easily affected by later alteration in areas with strong hydrothermal activity (such as Rb migration caused by mica alteration and Mg introduction by chloritization), resulting in abnormal deviations in the ratios and producing "high evolution illusion" or "low evolution misjudgment". (2) Although the "low temperature surrounding rock controlling mineralization" model corrects the traditional exploration direction—pointing out that when pegmatite intrudes into low temperature surrounding rocks (far from the parent rock body), the thermal lifetime is short (≤300℃), which can effectively inhibit the diffusion and loss of lithium and is conducive to the enrichment of minerals such as spodumene; while high temperature surrounding rocks (near the parent rock body) are subject to strong thermal disturbance, which causes lithium to migrate and dissipate along the mineral grain boundaries, resulting in a decrease in mineralization potential. While this model identifies low-temperature metamorphic zones as priority target areas, its core flaw lies in the fact that there is no necessary correlation between the temperature of the surrounding rock and the degree of evolution of the pegmatite itself. Low-temperature environments only provide conditions for mineral preservation but cannot indicate whether melt differentiation has reached the critical state of extraordinary enrichment of rare metals. In practice, there are common counterexamples where low-evolutionary pegmatites in low-temperature zones lack economic mineralization, while highly differentiated pegmatites in high-temperature zones can still form mineral deposits, highlighting the blind spot in judging sufficient mineralization conditions using a single surrounding rock indicator. Summary of the Invention

[0005] The purpose of this invention is to provide a method for judging the lithium mineralization potential of pegmatites using tourmaline, which can effectively reduce the mineral exploration cycle, minimize exploration costs, cause no environmental damage, ensure the accuracy of prediction, and greatly reduce exploration risks.

[0006] To solve the above-mentioned technical problems, the present invention adopts the following technical solution: A method for determining the lithium mineralization potential of pegmatites using tourmaline is provided, comprising the following steps: 1) Delineate mineralized areas Delineate favorable locations where pegmatite lithium mineralization potential may exist; 2) Sample collection In step 1), pegmatite samples containing a large amount of tourmaline were collected from the mineralized favorable area and probe slides were prepared. 3) Trace element analysis of tourmaline The contents of Li, Nb, Ta and FeO in tourmaline were analyzed, and the Nb / Ta ratio was calculated. 4) Li and B isotope analysis of tourmaline In-situ analyses of lithium and boron isotopes were performed at the locations of trace analysis in tourmaline, yielding δ¹⁸O⁻. 7 Li and δ 11 B; 5) Determination of mineralization potential Based on the tourmaline trace element, Li isotope, and B isotope data obtained in steps 3)-4), the same pegmatite vein or the same sample sequence was analyzed; the evolution sequence was divided into magmatic crystallization differentiation stage (FeO ≥ 6 wt%) and fluid exsolution stage (FeO < 6 wt%), with FeO content = 6 wt%. ① Determination of the degree of crystallization differentiation For samples from the magma crystallization differentiation stage (FeO ≥ 6 wt%), if the following conditions (a) to (e) are met simultaneously, the pegmatite system is considered to have undergone intense crystallization differentiation; if any of these conditions are not met, the degree of crystallization differentiation is insufficient, and the sample does not have the potential to form a lithium deposit. (a) FeO ≥ 6 wt%, and shows a continuous decreasing trend with the evolution process; (b) The Nb / Ta ratio decreases with decreasing FeO content, and in the late evolution stage when the FeO content is 6-8 wt%, the Nb / Ta ratio is ≤1.0 (indicating high differentiation). (c) The Li content increases as the FeO content decreases, and in the late evolution stage when the FeO content is 6-8 wt%, the Li content is ≥ 5000 ppm; (d) As FeO content decreases (evolutionary degree increases), δ 7 The Li value changes gradually, with the variation range (difference between the maximum and minimum values) ≤ 5.0‰ (i.e., no drastic oscillations). (e)δ 11 The B value remained stable between -14.0‰ and -10.0‰, and during the crystallization differentiation stage (FeO decreased from 15 wt% to 6 wt%), δ 11 The variation range of the B value (the difference between the maximum and minimum values) is ≤ 2.0‰, indicating that no significant fluid exsolution occurred during the crystallization differentiation process.

[0007] ② Determination of fluid exsolution Based on meeting the crystallization differentiation conditions described in step ①, further analysis was conducted on the sample during the fluid exsolution stage (FeO < 6 wt%). If the following changes occurred, it was determined that the pegmatite system underwent a fluid exsolution process in the late stage of crystallization differentiation: (a) δ during the fluid exsolution stage (FeO < 6 wt%) 11 The average value of B during the stage is higher than that of δ during the crystallization differentiation stage (FeO ≥ 6wt%). 11 The average value of B in each stage decreased by ≥ 1.5‰ (i.e., the difference in average value was ≥ 1.5‰). (b) The Li content in tourmaline further increased to ≥9000 ppm.

[0008] If δ 11 If the B value does not show the above significant decrease (the difference in the average value of each stage is less than 1.5‰), or the Li content does not reach 9000 ppm, it is judged that no effective fluid exsolution has occurred, and even if crystallization differentiation has occurred, it does not have the potential to form a lithium deposit.

[0009] ③ Comprehensive assessment of mineralization potential It has mineralization potential: This pegmatite system simultaneously satisfies the crystallization differentiation conditions of step ① and the fluid exsolution conditions of step ②.

[0010] No mineralization potential: If any condition in step ① is not met, or if step ① is met but step ② is not met.

[0011] According to the above scheme, in step 1), in the area where pegmatites are densely distributed, the existing geological, geophysical, geochemical and remote sensing data in the study area are systematically collected, and their mineralization potential is comprehensively analyzed to delineate favorable areas where pegmatite lithium mineralization potential may exist.

[0012] According to the above scheme, in step 2), samples of pegmatite containing a large amount of tourmaline are collected in the mineralized favorable area delineated in step (1). GPS positioning is used to collect coordinate data for each sampling point, field photos are taken, detailed field records are made, the lithology, alteration and mineralization characteristics of each sample are described, and probe slides are made.

[0013] According to the above scheme, in step 3), trace element analysis is performed using LA-ICP-MS.

[0014] According to the above scheme, in step 4), the GeoLas 2005 193 nm ArF excimer nanosecond laser ablation system is used in conjunction with the Neptune Plus multi-receiver inductively coupled plasma mass spectrometer (MC-ICP-MS) for in-situ analysis of lithium isotopes; the RESOlution S155-LR 193 nm laser ablation system is used in conjunction with the Neptune plus multi-receiver inductively coupled plasma mass spectrometer for in-situ analysis of B isotopes.

[0015] According to the above scheme, in step 5), during the magma crystallization differentiation stage, the FeO content ranges from 6 to 15 wt%.

[0016] The Li and B isotope and trace element assemblages of tourmaline have unique advantages in distinguishing between magma crystallization differentiation and fluid exsolution: B isotope changes caused by crystallization differentiation are usually controlled by Rayleigh fractionation, thus the trend is generally small. B isotopes are highly sensitive to fluid exsolution; during fluid exsolution, ¹¹B tends to enter the fluid, reducing the residual melt δ¹¹B, and its magnitude and trend are significantly different from those caused by crystallization differentiation. In contrast, Li isotope fractionation caused by simple crystallization differentiation and fluid exsolution is very small. Simultaneously, the trace element assemblages provide key constraints: during crystallization differentiation, Nb / Ta will decrease, and incompatible elements (such as Li) will gradually accumulate. Joint analysis of Li-B isotopes and trace elements can be used to determine the degree of crystallization differentiation and the extent of fluid exsolution: if, during the crystallization differentiation stage (FeO decreases from 15 wt% to 6 wt%), δ¹¹B... 7 Li and δ 11 B remains stable (with variations within the stages ≤5.0‰ and ≤2.0‰ respectively), with only incompatible elements (such as Li) gradually enriched, reflecting that crystallization differentiation is dominant; if in the fluid exsolution stage (FeO < 6 wt%), δ 11 If the average value of B decreases significantly by ≥1.5‰ compared to the crystallization differentiation stage, and the Li content rapidly increases to ≥9000 ppm, it indicates that fluid exsolution is dominant; if the above conditions are met simultaneously, it can be determined that the pegmatite system has mineralization potential.

[0017] The main beneficial effects of this invention are as follows: This invention provides a method for determining the lithium mineralization potential of pegmatites using tourmaline. By performing trace element and Li and B isotope analysis on tourmaline in pegmatites, the degree of crystal differentiation and fluid exsolution are determined, thereby assessing the mineralization potential of the pegmatites. This method can effectively reduce the mineral exploration cycle, minimize exploration costs, and has no environmental impact. The accuracy of the prediction is guaranteed, overcoming the difficulties of traditional methods, which have certain indirectness and guesswork. It provides a theoretical basis for mineral deposit-scale exploration, effectively reduces exploration risks, and has broad application prospects. Attached Figure Description

[0018] Figure 1 The graph shows the changes in Nb / Ta and FeO content in the ore-forming system of Example 1 and the non-ore-forming system of Example 2.

[0019] Figure 2 The graph shows the changes in Li and FeO content in the ore-forming system of Example 1 and the non-ore-forming system of Example 2.

[0020] Figure 3 δ in the ore-forming system of Example 1 and the non-ore-forming system of Example 2 7 Graph showing the changes in Li and FeO contents.

[0021] Figure 4 δ in the ore-forming system of Example 1 and the non-ore-forming system of Example 2 11 Graph showing the changes in B and FeO content. Detailed Implementation

[0022] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0023] This invention provides a method for determining the lithium mineralization potential of pegmatites using tourmaline, comprising the following steps: 1) Delineate mineralized areas In areas with dense pegmatite distribution, existing geological, geophysical, geochemical, and remote sensing data were systematically collected and comprehensively analyzed to determine their mineralization potential and to delineate favorable locations where pegmatite may have lithium mineralization potential.

[0024] 2) Sample collection In step (1), pegmatite samples containing a large amount of tourmaline were collected from the mineralized favorable areas. GPS positioning was used to collect coordinate data for each sampling point, field photos were taken, detailed field records were made (describing the lithology, alteration and mineralization characteristics of each sample), and probe slides were prepared.

[0025] 3) Trace element analysis of tourmaline The contents of Li, Nb, Ta and FeO in tourmaline were analyzed using LA-ICP-MS, and the Nb / Ta ratio was calculated.

[0026] 4) Li isotope analysis of tourmaline In-situ analysis of lithium isotopes was performed at the location of tourmaline trace analysis using a GeoLas 2005 193 nm ArF excimer nanosecond laser ablation system coupled with a Neptune Plus multi-receiver inductively coupled plasma mass spectrometer (MC-ICP-MS). To suppress matrix effects, a water-assisted method was employed, continuously introducing ultrapure water (approximately 3.68 μL·min⁻¹) before the laser ablation cell to create wet plasma conditions. The selected laser beam diameter was 44 μm, energy density was 4 J / cm², and frequency was 6 Hz. Mass fractionation correction of the data employed a sample-standard cross-analysis method, where a standard sample was analyzed before and after each test sample, and the average mass discrimination of the standard samples was used to correct the sample test results. The laboratory used NIST 610 glass as the external calibration standard (δ¹⁰). 7 The Li reference value was 32.6 ± 0.30‰ (measured by SN-MC-ICP-MS) and non-matrix-matched calibration was performed. Sample IAEA-B-4 was used as a monitor sample to control data quality, and monitoring was performed every 5 sample points analyzed. The δ of IAEA-B-4... 7 The reference value for Li is 5.64 ± 0.41‰ (Lin et al., 2019). The test result for the monitored sample IAEA-B-4 was 5.63 ± 0.79‰ (n = 26, 2SD), which is consistent with the reference value within the error range.

[0027] 5) Tourmaline B isotope analysis In-situ analysis of boron isotopes was performed at the location of trace analysis in tourmaline using a RESOlution S155-LR 193 nm laser ablation system coupled with a Neptune plus multi-receiver inductively coupled plasma mass spectrometer. The selected laser beam diameter was 44 μm, energy density was 3.5 J / cm², and frequency was 5 Hz. Mass fractionation correction of the data employed a sample-standard cross-analysis method, where a standard sample was analyzed before and after each test sample, and the average mass discrimination of the standard samples was used to correct the sample test results. The laboratory used the standard material IMR-RB1 developed by the Institute of Mineral Resources, Chinese Academy of Geological Sciences, for external standard correction of data mass fractionation. Sample 112566-Schorl was used as a monitoring sample to control data quality, monitored once after every five sample points analyzed. The δ¹¹B reference value for 112566-Schorl is [value missing]. 12.5 ± 0.57‰ (Hou et al., 2010; Ishikawa et al., 2001; Ishikawa and Tera, 1997). The test results for monitored sample 112566-Schorl were... 12.4‰ ± 0.90‰ (n = 60, 2SD), consistent with the reference value within the error range.

[0028] 6) Determination of mineralization potential Based on the tourmaline trace element, Li isotope, and B isotope data obtained in steps 3)-5), the same pegmatite vein or the same sample sequence was analyzed. Using FeO content = 6 wt% as the boundary, the evolution sequence was divided into a magmatic crystallization differentiation stage (FeO ≥ 6 wt%) and a fluid exsolution stage (FeO < 6 wt%), and the distinction was made sequentially according to the following three steps: ① Determination of the degree of crystallization differentiation For samples from the magma crystallization differentiation stage (FeO ≥ 6 wt%), if the sample simultaneously meets the following conditions (a) to (e), it is determined that the pegmatite system has undergone intense crystallization differentiation; if any of the conditions are not met, it is determined that the degree of crystallization differentiation is insufficient and it does not have the potential to form a lithium deposit. (a) The Nb / Ta ratio decreases with decreasing FeO content, and in the late evolution stage when the FeO content is 6-8 wt%, the Nb / Ta ratio is ≤ 1.0; (b) The FeO content ranged from 6 to 15 wt%, and showed a continuous decreasing trend with the evolution process; (c) The Li content increases as the FeO content decreases, and when the FeO content drops to 6-8 wt% (late stage), the Li content is ≥ 5000 ppm; (d) As FeO content decreases (evolutionary degree increases), δ 7 The Li value changes gradually, with the variation range (difference between the maximum and minimum values) ≤ 5.0‰ (i.e., no drastic oscillations). (e)δ 11 The B value remained stable between -14.0‰ and -10.0‰, and during the crystallization differentiation stage (FeO decreased from 15 wt% to 6 wt%), δ 11 The variation range of the B value (the difference between the maximum and minimum values) is ≤ 2.0‰, indicating that no significant fluid exsolution occurred during the crystallization differentiation process.

[0029] Note: Conditions (a) to (c) above are the main quantitative indicators, and conditions (d) and (e) are auxiliary verification indicators. In practical applications, if all conditions (a) to (c) are met and the trends of (d) and (e) are consistent, it can be determined as strong crystallization differentiation.

[0030] ② Determination of fluid exsolution Based on meeting the crystallization differentiation conditions described in step ①, further analysis was conducted on the sample during the fluid exsolution stage (FeO < 6 wt%). If the following changes occurred, it was determined that the pegmatite system underwent a fluid exsolution process in the late stage of crystallization differentiation: (a) δ during the fluid exsolution stage (FeO < 6 wt%) 11 The average value of B during the stage is higher than that of δ during the crystallization differentiation stage (FeO ≥ 6wt%). 11 The average value of B in each stage decreased by ≥ 1.5‰ (i.e., the difference in average value was ≥ 1.5‰). (b) At the same time, the Li content in tourmaline further increases to ≥ 9000 ppm.

[0031] If δ 11 If the B value does not show the above-mentioned significant decrease (change range <1.5‰), or the Li content does not reach 9000 ppm, it is judged that no effective fluid exsolution has occurred, and even if crystallization differentiation has occurred, it does not have the potential to form a lithium deposit.

[0032] ③ Comprehensive assessment of mineralization potential It has mineralization potential: This pegmatite system simultaneously satisfies the crystallization differentiation conditions of step ① and the fluid exsolution conditions of step ②.

[0033] No mineralization potential: If any condition in step ① is not met, or if step ① is met but step ② is not met.

[0034] The following are specific examples: Example 1: Determination of mineralization potential of pegmatite in a certain area Trace element and Li and B isotope analyses were performed on tourmaline in pegmatite from a certain region. Specific results are shown below. Figure 1-4 (Red dot), the measurement results show: 1) Identification of magma crystallization differentiation stages (FeO ≥ 6 wt%): The FeO content decreased continuously from 13.8 wt% to approximately 6.0 wt%. The Nb / Ta ratio in tourmaline decreases with decreasing FeO, gradually dropping from approximately 3.17 to below 1.0. The Li content gradually increased from 480 ppm to approximately 5000-7000 ppm; δ 7 The Li value ranged from 16.9‰ to 21.1‰, with a range of 4.2‰ (≤5.0‰) within the period. The data points changed continuously without drastic oscillations. δ 11 The B value slowly changes from about -10.5‰ to about -12.5‰ during the crystallization differentiation stage (with fluctuations within the stage ≤ 2.0‰), which is a gradual change in the crystallization differentiation process.

[0035] The above characteristics indicate that this pegmatite system underwent intense magmatic crystallization differentiation.

[0036] 2) Determination of fluid exsolution stage (FeO < 6 wt%): The FeO content further decreased to 1.1–5.7 wt%; After entering the fluid exsolution stage, δ 11 The average value of stage B (approximately -13.4‰) is about 1.6‰ lower than that of the crystallization differentiation stage (approximately -11.8‰) (≥1.5‰), showing a sudden change across stages; The Li content rapidly increased to over 9000 ppm, reaching a maximum of 10059 ppm; The Nb / Ta ratio was generally in the low range (0.11~1.28) during the fluid exsolution stage, with the vast majority of samples having a ratio <1.0.

[0037] The above characteristics indicate that the pegmatite system underwent fluid exsolution during the late stage of magma crystallization differentiation.

[0038] Based on comprehensive assessment, this pegmatite system simultaneously meets the conditions for magma crystallization differentiation and fluid exsolution, and is therefore determined to have the potential to form a lithium deposit.

[0039] Example 2: Determination of mineralization potential of pegmatite in a certain area Trace element and Li and B isotope analyses were performed on tourmaline in pegmatite from a certain region. Specific results are shown below. Figure 1-4 (Black dot), the measurement results show: The FeO content ranged from 14.3 to 17.4 wt%, all of which were greater than 6 wt%, and no samples had FeO < 6 wt%. The Li content was consistently below 200 ppm, far from reaching 5000 ppm; δ 7 The Li value ranges from 10.6 to 14.9‰; δ 11 The B value remained stable between -13.6‰ and -11.6‰, without any cross-stage mutations that resulted in a decrease in the stage mean of ≥1.5‰.

[0040] The above characteristics do not meet the key threshold in the criteria for judging the degree of magma crystallization differentiation (Li content < 5000 ppm and no evolutionary samples with FeO < 6 wt%). Therefore, there is no need to proceed to the fluid exsolution discrimination. It can be directly determined that the degree of crystallization differentiation of this pegmatite system is insufficient and it does not have the potential to form a lithium deposit.

[0041] Sample analysis results in the two systems

[0042] It should be understood that those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of the appended claims.

Claims

1. A method for determining the lithium mineralization potential of pegmatites using tourmaline, characterized in that, Includes the following steps: 1) Delineate mineralized areas Delineate favorable locations where pegmatite lithium mineralization potential may exist; 2) Sample collection Collect pegmatite samples containing a large amount of tourmaline from the designated favorable mineralization areas and prepare probe slides; 3) Trace element analysis of tourmaline The contents of Li, Nb, Ta and FeO in tourmaline were analyzed, and the Nb / Ta ratio was calculated. 4) Li and B isotope analysis of tourmaline In-situ analyses of lithium and boron isotopes were performed at the locations of trace analysis in tourmaline, yielding δ¹⁸O⁻. 7 Li and δ 11 B; 5) Determination of mineralization potential The evolutionary sequence was divided into a magmatic crystallization differentiation stage and a fluid exsolution stage based on FeO content, corresponding to FeO ≥ 6 wt% and FeO < 6 wt%, respectively; where: ① Determination of the degree of crystallization differentiation For samples of magma with FeO ≥ 6 wt% in the crystallization differentiation stage, if the following conditions a) ~ e) are met simultaneously, it is determined that they have undergone intense crystallization differentiation. a) FeO ≥ 6 wt%, and shows a continuous decreasing trend with the evolution process; b) The Nb / Ta ratio decreases with decreasing FeO content, and when the FeO content drops to 6-8 wt%, the Nb / Ta ratio is ≤1.0; c) The Li content increases as the FeO content decreases, and when the FeO content drops to 6~8wt%, the Li content is ≥5000ppm; d) As the FeO content decreases, δ 7 The Li value changes gradually, with a variation range of ≤5.0‰; e)δ 11 The B value remained stable between -14.0‰ and -10.0‰, with a variation range of ≤2.0‰; ② Determination of fluid exsolution Based on meeting the crystallization differentiation conditions in step ①, further analysis was conducted on samples with FeO < 6 wt% during the fluid exsolution stage. If the following conditions were met simultaneously, it was determined that fluid exsolution occurred in the late stage of crystallization differentiation: a) δ during the fluid exsolution stage 11 The average value of B during the stage is compared with the δ value during the crystallization differentiation stage. 11 The average value of B decreased by ≥1.5‰ over the period. b) The Li content in tourmaline further increased to ≥9000 ppm; ③Comprehensive assessment of mineralization potential If a pegmatite system simultaneously satisfies the crystallization differentiation conditions of step ① and the fluid exsolution conditions of step ②, it has mineralization potential.

2. The method according to claim 1, characterized in that, In step 1), in areas with dense pegmatite distribution, existing geological, geophysical, geochemical, and remote sensing data are systematically collected, and their mineralization potential is comprehensively analyzed to delineate favorable areas where pegmatite lithium mineralization potential may exist.

3. The method according to claim 1, characterized in that, In step 2), pegmatite samples containing a large amount of tourmaline are collected from the mineralized favorable area delineated in step 1. GPS positioning is used to collect coordinate data for each sampling point, field photos are taken, detailed field records are made, the lithology, alteration and mineralization characteristics of each sample are described, and probe slides are made.

4. The method according to claim 1, characterized in that, In step 3), trace element analysis is performed using LA-ICP-MS.

5. The method according to claim 1, characterized in that, In step 4), an in-situ analysis of lithium isotopes was performed using a GeoLas 2005 193 nm ArF excimer nanosecond laser ablation system coupled with a Neptune Plus multi-receiver inductively coupled plasma mass spectrometer; an in-situ analysis of B isotopes was performed using a RESOlution S155-LR 193 nm laser ablation system coupled with a Neptune plus multi-receiver inductively coupled plasma mass spectrometer.

6. The method according to claim 1, characterized in that, In step 5), during the magma crystallization differentiation stage, the FeO content ranges from 6 to 15 wt%.

7. The method according to claim 1, characterized in that, In step 5), when judging the degree of crystal differentiation, if any one of the conditions is not met, it is judged that the degree of crystal differentiation is insufficient and that it does not have the potential to form a lithium deposit.

8. The method according to claim 1, characterized in that, In step 5), when determining the fluid exsolution effect, if δ 11 If the average difference in the B-value stage is less than 1.5‰, or the Li content does not reach 9000 ppm, it is determined that no effective fluid exsolution has occurred, and even if crystallization differentiation has occurred, it does not have the potential to form a lithium deposit.